A dictionary and grammatical sketch of Dagaare (Volume 4) - Ali, Mark (Language Science Press, 2021)
This book presents an extensive dictionary of the Dagaare language (Niger-Congo; Gur (Mabia)), focussing on the dialect of Central Dagaare, spoken in the Upper West region of Ghana. The dictionary provides comprehensive definitions, example sentences and the English translations, phonetic forms, inflected forms, etymological notes as well as information dialectal variation. This work is intended as a resource for linguists, but also as a resource for Dagaare speakers. Also included is a grammatical sketch of Dagaare contributed by Prof. Adams Bodomo.